Dukungan Sosial sebagai Moderator Kecemasan Kematian dan Depresi pada Tenaga Medis Covid-19 - Gusbet, Rani Attiqah (INSAN Jurnal Psikologi dan Kesehatan Mental, 2023)
Close contact with patients makes healthcare workers have a higher risk to infection and death. Death anxiety and depression might have an impact on the performance of healthcare workers during taking care of the patients. Regression analysis were performed to evaluate the moderating role of social support on the relationship between death anxiety and depression. The aim of this study was to analyze the role of social support as a moderator of the relationship between death anxiety and depression in healthcare workers during the Covid-19 pandemic. This study uses an online survey conducted to 192 healthcare workers in a few cities in Indonesia. This data was measured using the PHQ-9, DAS-E, and MSPSS scales. The data were analyzed by moderated regression analysis. The results of this study indicate that social support does not moderate the relationship between death anxiety and depression in healthcare workers during the Covid-19 pandemic.